PENGARUH PENDAPATAN DAN BELANJA TERHADAP PERTUMBUHAN EKONOMI, KEMISKINAN DAN PENGANGGURAN (Studi Pada APBN 2004-2008) - Rudiningtyas, Dyah Arini (Fakultas Ekonomi, UIN Maliki Malang, 2011)
APBN is the budget of country every period that describes government’s capability and authority conducting the function of administration to reach the purpose of country. The purpose of this research is to examine the effect of revenue toward economy growth, the effect of expense toward economy growth, the effect of revenue toward poverty, the effect of expense toward poverty and the effect of revenue toward unemployment, the effect of expense toward unemployment. Sample of this research is APBN and realization of APBN from 2004 up to 2008. The same year also prevails for the level of economy growth, poverty, and unemployment. The period of this research is 2004-2008. The method applied in this study is the simple linier regression analysis by using SPSS program 15.0 version for windows. The result of this research shows that revenue does not have significant effect toward economy growth, expense does not have significant effect toward economy growth, revenue has significant effect toward poverty, expense has significant effect toward poverty, revenue does not have significant effect toward unemployment, and expense does not have significant effect toward unemployment.